(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Kovalʹchuk O. L. Problems of using new pedagogical technologies in achieving successful experiences in modern cases. This article is deals with a problems of use modern technologies for preparation of future competent specialists of speciality «Organization of air transportations» of air industry.